1998
DOI: 10.2337/diacare.21.4.487
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of Plasma Lipid Peroxides, Monocyte Adhesion, and Tumor Necrosis Factor-α Production in NIDDM Patients After Gliclazide Treatment

Abstract: Gliclazide administration to NIDDM patients inhibits the increased adhesiveness of diabetic monocytes to endothelial cells and reduces the production of TNF-alpha by these cells. These results suggest that treatment of NIDDM subjects with gliclazide may be beneficial in the prevention of atherosclerosis associated with NIDDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
1
22

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 0 publications
2
64
1
22
Order By: Relevance
“…To date, only in vitro or ex vivo studies have been done that showed the inhibitory effects of gliclazide, a sulphonylurea hypoglycaemic drug, on enhanced adhesion of leukocytes to endothelial cells in high glucose conditions [16,17,18]. In this study, we clearly demonstrated the inhibition of leukostasis in the diabetic retina in vivo by gliclazide, but not by another sulphonylurea drug, glibenclamide, supporting these previous in vitro and ex vivo studies [16,17,18] and explaining the observation in the previous clinical studies [21,22] in which gliclazide actually showed a preventive effect on progression of diabetic retinopathy compared with other sulphonylurea drugs in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, only in vitro or ex vivo studies have been done that showed the inhibitory effects of gliclazide, a sulphonylurea hypoglycaemic drug, on enhanced adhesion of leukocytes to endothelial cells in high glucose conditions [16,17,18]. In this study, we clearly demonstrated the inhibition of leukostasis in the diabetic retina in vivo by gliclazide, but not by another sulphonylurea drug, glibenclamide, supporting these previous in vitro and ex vivo studies [16,17,18] and explaining the observation in the previous clinical studies [21,22] in which gliclazide actually showed a preventive effect on progression of diabetic retinopathy compared with other sulphonylurea drugs in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Gliclazide could have certain non-metabolic effects specifically related to vascular function, which other sulphonylurea agents might not have [13,14,15,16,17,18,32,33,34]. For example, gliclazide was reported to have free-radical scavenging activity [13,14,15,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with type-2 diabetes mellitus, glibenclamide administration inhibits increased monocyte adhesion to endothelial cells, thus decreasing TNF-α production by these cells 30 . In mice, glibenclamide did not have an effect on the production of TNF-α and had very little effect on the activity of this cytokine, according to Fukuzawa et al 31 .…”
Section: Serum Concentrations and Renal Expressions Of Il-1 And Tnf-amentioning
confidence: 99%